IMPACT OF HUMOUR ELEMENT OF ADVERTISEMENT IN CONSUMER PURCHASING DECISION - Rangasamy, Satheeshkumar; C., Sachana; P, Kavyanjali; R, Gunashekar (International Journal of Research -GRANTHAALAYAH, 2025)
Humour has been widely acknowledged as an effective strategy in advertising, capable of capturing consumer attention and shaping their purchasing choices. The impact of humour on customr purchasing decisions is affected by the consumer's involvement or attachment to the product. When promoting a new product, humorous advertisements can capture the consumer's attention and access the consumer's long-term memory better than the non-humorous ones. It's vital to remember that using humour in advertising isn't a one-size-fits-all solution. Different audiences have different tastes and sensitivity to humour. Advertisers must assess the market’s demographic, cultural factors and the suitability of humour in relation to their brand and product. Furthermore, to establish a unified and effective campaign, humour should always connect with the overall advertising message and the intended company image. It is critical to note that humour can be quite powerful in changing a consumer's thinking about a given product. It was discovered that the hilarious nature of advertisements increased attention when compared to non-humorous advertisements. Data was collected through questionnaire using primary data collection method on five-point Likert scale from 350 respondents. The researcher uses the convenience and snowball sampling technique for the collection of data. The nature of this study is descriptive. The association of humour in advertising with consumer purchase intention was studied. It was concluded that humour in advertising has a significant impact on consumer purchase intention.